Enzymatic hydrolysis of delignified bagasse polysaccharides - Adsul, Mukund G.; Ghule, J. E.; Shaikh, H.; Singh, R.; Bastawade, Kulbhushan B.; Gokhale, D. V.; Varma, Anjanikumar (Carbohydrate Polymers, 2005)
Sugarcane bagasse, consisting of cellulose, xylan, and lignin, was chemically treated to generate bagasse samples with continuously decreasing content of lignin. These bagasse samples were hydrolyzed by cellulase and xylanase enzymes, produced earlier by Penicillium janthinellum NCIM 1171 in the same bagasse polysaccharides production medium. The hydrolysis was carried out by using different concentrations of the enzymes at two different temperatures, 30 and 50 degrees C, taking hydrolysis of Avicel as control. It was found that while the maximum hydrolysis for Avicel was 70% that of some of the bagasse polysaccharides was as high as 95%. The products of hydrolysis were glucose, xylose, and arabinose, as confirmed by high pressure ion chromatography (HPIC). It is interesting to note that arabinose, which constitutes about 10% of the weight of bagasse xylan, could also be released easily by the enzymes. Also, the initial rates of hydrolysis was found to be much higher for the bagasse polysaccharides, and in some cases about 90% of the hydrolysis occurred within 20 h. Amongst all bagasse samples, the sample with (Kappa no. 1.2, lignin content 0.18%) gave the highest degree of hydrolysis at 50 degrees C. Even the bagasse polysaccharide with Kappa no. 16.8 (lignin content 2.5%) underwent greater extent of hydrolysis than Avicel. Apparently, the delignified bagasse medium appears to be a facile medium for the combined hydrolytic action of the cellulase and xylanase enzymes. Considering that sugarcane bagasse is a waste biomass material available in abundance annually, this methodology can be used to value-add to this biomass to produce sugars, which can be fermented to produce biofuels like ethanol. (C) 2005 Elsevier Ltd. All rights reserved.
Keywords: bagasse polysaccharides; Cellulase; chemical treatment; Enzymatic hydrolysis; Penicillium janthinellum; Sugarcane bagasse; Xylanase

Lignin-carbohydrate complexes from sugarcane bagasse: preparation, purification, and characterization - Singh, R.; Singh, S.; Trimukhe, K. D.; Pandare, K. V.; Bastawade, Kulbhushan B.; Gokhale, D. V.; Varma, Anjanikumar (Carbohydrate Polymers, 2005)
Lignin-carbohydrate complexes were isolated from sugarcane bagasse by a process, which yielded sulfur-free lignins. These could be made carbohydrate-free, if necessary, by treatment with xylanase enzyme. A study of the preparation, purification, and characterization of such lignin-carbohydrate complexes, comparison with commercial lignin samples (wood based as well as bagasse based) and some other lignin derivatives was made by using a variety of analytical tools such as FTIR, HPLC at three different UV-wavelengths, GPC, thermal analysis and elemental analysis. The use of such a diverse range of lignin-carbohydrate complex samples enabled us to predict the sensitivity of the various analytical techniques for characterization of complex polymers containing carbohydrate moieties. Evidence for lignin-carbohydrate complex was detectable by FTIR as well as HPLC studies. Thermal analysis studies showed the crucial effect of carbohydrate groups, the content of aliphatic chains, and the sulfur content of the lignins. Generalized structures of lignin-carbohydrate complexes obtained from various sources using different preparation methods and chemical modifications are presented. This will aid the applications development effort with advantageously using lignins containing low levels of carbohydrate moieties as reactive sites as well as biodegradability inducing sites. (C) 2005 Elsevier Ltd. All rights reserved.
Keywords: biodegradability; hardwood lignins; lignin-carbohydrate complex; softwood lignins; Sugarcane bagasse; sulfur-free lignins; xylanase enzyme